Occupational health risk of farmers: A qualitative study with the agriculture society of trinidad and tobago and the ministry of agriculture, land and fisheries - Barry Parasram; Avishek Choudhury (PLoS ONE, 2025)
The agriculture sector is significantly affected by pesticide toxicity, leading to fatal and chronic diseases. The objective of this research is to explore the perception of the farmers, the representatives of the Agriculture Society of Trinidad and Tobago (ASTT), and the officials of the Ministry of Agriculture, Land and Fisheries (MALF) on the protection of farmers, particularly on the exposure to pesticides in Trinidad and Tobago. We conducted face-to-face, semi-structured interviews with 32 individuals from the MALF and ASTT. Interviews were analyzed using inductive thematic analysis and deductive reasoning. Responses reveal six themes: (a) Barriers to Proper Use of Personal Protective Equipment (PPE); (b) Challenges in Safe Chemical Use and Disposal Practices; (c) Health Impacts of Unsafe Chemical Exposure, (d) Challenges in Farmer Training and Adoption of Safety Practices; (e) Lack of Policies and Monitoring for Farmer Safety and Chemical Use; (f) Absence of Quality Control and Unsafe Practices in Local Produce. A consistent finding suggested an interplay between limited safety awareness, entrenched cultural practices, and the absence of rigorous policy enforcement. Farmers, Ministry of Agriculture officials, and industry representatives acknowledge that while isolated instances of good practice exist, these are overshadowed by regulatory oversight. Farmers remain at significant risk of adverse health outcomes, and consumers may face potential hazards from unmonitored chemical residues in local food. Our research highlights the urgent need for better safety regulations, more effective training, and the establishment of monitoring systems to protect the health of farmers and ensure safe agricultural practices. By shedding light on these issues, this study paves the way for developing targeted interventions to improve farmer health and safety standards in Trinidad and Tobago’s agricultural sector.